2006
DOI: 10.3164/jcbn.38.188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Garcinia cambogia Administration on Female Reproductive Organs in Rats

Abstract: Summary We investigated the effect of administering Garcinia cambogia (GA), which contains (−)-hydroxycitric acid ((−)-HCA), to female rats, focusing especially on changes in sexual hormones and its safety in terms of histopathological changes. A diet containing a high level of (−)-HCA (154 mmol / kg diet) was given to seven-week-old female rats with matched estrous cycles for two or four weeks. There were no significant differences in any of the serum hormones tested (follicle-stimulating hormone, luteinizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In a continuation to the study conducted by Saito et al [ 26 ], Kiyose et al [ 27 ] investigated the cause of impaired spermatogenesis due to ingestion of G. cambogia powder (containing 41.2 wt% of (−)-HCA, the ratio of free to lactone form was 36.6 to 63.4) at 102 mmol/kg diet in young Fischer 344 male rats. By considering that 4,4-dimethyl-5 α -cholesta-8,24-diene-3 β -ol, a testis meiosis-activating sterole (T-MAS), was a specific intermediate product of cholesterol biosynthesis in testicular germ cells, the authors elucidated the relationship between impaired spermatogenesis and MAS production in rats testis, postingestion of G. cambogia .…”
Section: In Vitro and In Vivo mentioning
confidence: 99%
See 1 more Smart Citation
“…In a continuation to the study conducted by Saito et al [ 26 ], Kiyose et al [ 27 ] investigated the cause of impaired spermatogenesis due to ingestion of G. cambogia powder (containing 41.2 wt% of (−)-HCA, the ratio of free to lactone form was 36.6 to 63.4) at 102 mmol/kg diet in young Fischer 344 male rats. By considering that 4,4-dimethyl-5 α -cholesta-8,24-diene-3 β -ol, a testis meiosis-activating sterole (T-MAS), was a specific intermediate product of cholesterol biosynthesis in testicular germ cells, the authors elucidated the relationship between impaired spermatogenesis and MAS production in rats testis, postingestion of G. cambogia .…”
Section: In Vitro and In Vivo mentioning
confidence: 99%
“…In addition, they indicated that Zucker rat may not be an appropriate model to evaluate testicular toxicity as obese male Zucker rat has a defect in testicular testosterone production [ 32 ]. The same question of whether the toxicity was possibly due to the atypical form of HCA containing 63% lactone could be applied on the study conducted by Kiyose et al [ 27 ]. Therefore, the claim of HCA in affecting the functionality of testis is yet to be concluded.…”
Section: In Vitro and In Vivo mentioning
confidence: 99%
“…This may reduce physical fatigue if energy deficiency is a cause of fatigue. Before hydroxycitric acid (HCA) was a promising anti-fatigue substance by inhibiting ATP citrate lyase with citric acid [ 9 ], but recently it was reported Garcinia cambogia containing HCA had reproductive toxicity [ 10 , 11 ], so citric acid is superior to HCA as an anti-fatigue substance in the respect of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the previous study , significant changes in serum hormone levels related to spermatogenesis (decrease in inhibin B and increase in FSH concentrations) were reported in HCA‐treated animals compared to the control group. When the same G. cambogia extract (HCA content 41.2%) was tested in female rats, no changes in sex hormones (FSH, LH, estradiol, and progesterone) and no morphological signs of toxicity in the follicle and corpus luteum were observed after feeding the animals a diet containing 154 mmol HCA/kg diet (a dose that induced marked testicular toxicity in the subchronic toxicity study ) for a period of 28 days .…”
Section: Hydroxycitric Acid (Hca)mentioning
confidence: 99%